The Effect of Gibberellin Hormone Concentration dan Soaking Duration on The Vigor Indeks of Black Glutinous Rice Seeds (Oryza sativa Linn Var. glutinousa) Expired - Christy, Arifah; Noficandra, Habibullah; Violita, Violita (Jurnal Serambi Biologi, 2023)
This study aims to determine the best concentration of gibberellin hormone and soaking duration for increasing the viability of expired black glutinous rice seeds. The study was conducted using a complete randomized design (RAL) with a two-factor treatment. The first factor related to variations in the concentration of gibberellin hormone is 0%, 1.5%, 2%, 2.5%, and 3%. The second factor is related to the length of soaking with variations of 12 hours, 24 hours, and 48 hours. Each treatment is carried out in 4 repetitions with parameters of vigor index. The results of this study showed that the treatment of varying concentrations of gibberellin hormone and variations in soaking time showed a significant effect on the control group (p <0.05) germination of expired black glutinous rice seeds Key words : Rice seeds, Expiration, Gibberellin hormone, Germination, Vigor Index